Bird of Many Plumes: Conceptions and Applications of Authority in the Thought of William of Saint–Thierry - Conzelmann, Delphine (Late Antiquity and Medieval Studies E-Books Online, Collection 2025, 2025)
Delphine Conzelmann unpacks the rich interplay of authority, tradition, and innovation in the works of William of Saint–Thierry, Benedictine abbott and Cistercian monk, whose contributions to Christian history were long overshadowed by those of his contemporaries. The volume seeks to reconcile seemingly contradictory aspects of this distinctive 12th–century biography, revealing what intention unites his stark criticism of new dialectic methods, his enthusiastic embrace of monastic reform, and his quest for reclusion. Discover the spiritual depth and doctrinal genius of William of Saint–Thierry in this comprehensive study